Differentiation Potential of Mouse Embryonic Stem Cells into Insulin Producing Cells in Pancreatic Islet Microenvironment - Yilmaz, I.; Sariboyaci, A. E.; Subasi, C.; Karaoz, E. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Background: The differentiation capacity of embryonic stem cells (ESCs) has great promise for type-1 diabetes for cellular treatment. Therefore, different strategies have been reported so far for derivation of insulin producing cells (IPCs) from ESCs. Providing similar microenvironmental conditions as in vivo, functional differentiation of stem cells into desired cell types could be obtained in vitro. The aim of the present research was to utilize differentiation potential of ESCs to IPCs by co-culture with mouse pancreatic islets (mPIs) for the first time.Methods: We present an in-direct differentiation protocol which compared with a conventional differentiation protocol. Novel in-direct co-culture differentiation protocol in which mPIs induced differentiation of ESCs into IPCs was used. This technique was compared with the chemical differentiation protocol that involved supplementing the differentiation media with specific growth factors. We analyzed differentiated cells in both groups by immune labelling, gene expression and protein secretion.Results: IPCs were obtained with in-direct co-culture within 30 days. Differentiated ESCs were found to be positive for IPC specific markers, Pdx1, Insulin, C-peptide, Glut2 and MafA. The results of immunocytochemical and gene expression analysis showed higher differentiation efficiency in co-culture group than chemical differentiation group. These results were confirmed by the response assay to high glucose levels with ELISA for insulin.Discussion: Our findings illustrate the significant effect of co-culture in different stages of differentiation and maturation of ESCs in vitro. We have developed an efficient and easy way to differentiate ESCs into IPCs, which possess similar characters of mature insulin positive cells.
Keywords: differentiation; co-culture; microenvironment; mouse pancreatic islets; embryonic stem cells; insulin producing cells